Pedagogical Innovations as Technologies for Developing Intercultural Communication - Mubinaxon, Yusufova; Abdumutaljonovna, Pakirdinova Sharofat (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
This article examines the theoretical and practical foundations of technologies for developing intercultural communication through pedagogical innovations. The study analyzes the effectiveness of interactive methods, project-based learning, and digital collaboration technologies within a competency-based approach through experimental research. The findings indicate that innovative pedagogical technologies significantly enhance students’ communicative activity, tolerance, empathy, and level of cultural awareness. The results confirm that integrating an intercultural component into the educational process plays a crucial role in shaping global thinking and developing the social adaptability of the younger generation.